1998
DOI: 10.1152/ajpregu.1998.274.6.r1789
|View full text |Cite
|
Sign up to set email alerts
|

High-energy turnover at low temperatures: recovery from exhaustive exercise in Antarctic and temperate eelpouts

Abstract: Earlier work on Notothenioids led to the hypothesis that a reduced glycolytic capacity is a general adaptation to low temperatures in Antarctic fish. In our study this hypothesis was reinvestigated by comparing changes in the metabolic status of the white musculature in two related zoarcid species, the stenothermal Antarctic eelpout Pachycara brachycephalum and the eurythermal Zoarces viviparus during exercise and subsequent recovery at 0°C. In both species, strenuous exercise caused a similar increase in whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
5
20
0
3
Order By: Relevance
“…A Q 10 with a similar value, around 9, has been calculated for the Antarctic eelpout Pachycara brachycephalum at 3-9ºC (Hardewig et al, 1998). It is therefore possible to assume a greater effect of temperature limiting the oxygen consumption for the sluggish Subantarctic eelpout in this thermal range.…”
Section: Discussionsupporting
confidence: 58%
“…A Q 10 with a similar value, around 9, has been calculated for the Antarctic eelpout Pachycara brachycephalum at 3-9ºC (Hardewig et al, 1998). It is therefore possible to assume a greater effect of temperature limiting the oxygen consumption for the sluggish Subantarctic eelpout in this thermal range.…”
Section: Discussionsupporting
confidence: 58%
“…pH i would be significantly decreased to 7.19 and ͉dG/d͉ would drop to below 44·kJ·mol -1 in the radial fibre compartment of the mantle organ. These calculations correspond to similar ͉dG/d͉ values for mantle muscle of three species of squid following fatiguing exercise, which ranged from 42 to 47·kJ·mol -1 , while values for two species of exercise-fatigued eelpout (P. brachycephalum, Z. viviparous) (Hardewig et al, 1998) white muscle ranged from 46.6 to 48·kJ·mol -1 . Possibly, reductions in the free energy of ATP hydrolysis as calculated for cuttlefish radial muscle could contribute to muscle fibre fatigue in that vital muscle due to functional impairments of ATPase functions.…”
Section: High T Csupporting
confidence: 67%
“…The consequent drop in pH i indicated that anaerobic metabolism was also being used to maintain ATP concentrations. Both Pörtner et al and Hardewig et al (Hardewig et al, 1998) have argued that as the cytosol becomes more acidic and, more importantly, as the phosphagen (PCr in case of fish) is lysed to Pi and Cr, there is a drop in ⌬G/d ATP . For two species of Zoarcid eelpouts, the free energy of ATP hydrolysis was observed to drop from -60·kJ·mol -1 to approximately -46·kJ·mol -1 and for rainbow trout, ⌬G/d ATP dropped from -60 to -47·kJ·mol -1 after exhaustive exercise (Hardewig et al, 1998).…”
Section: Fatiguementioning
confidence: 99%
“…Building on previous work (Hibberd et al, 1985), Debold et al add that inorganic phosphate and H + also reduce the force generated by cross-bridge cycling (Debold et al, 2004). Others have argued that a drop in the Gibbs free energy of ATP hydrolysis (dG/d ATP ) below a certain threshold results in fatigue (Hardewig et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation